2018
DOI: 10.1002/joc.5962
|View full text |Cite
|
Sign up to set email alerts
|

Heat waves in Berlin and Potsdam, Germany – Long‐term trends and comparison of heat wave definitions from 1893 to 2017

Abstract: Heat waves (HWs) are natural hazards characterised by episodes of hot weather. However, in the absence of a universal definition a wide variety of definitions is applied. In this study, ten different air temperature (T) based HW definitions are applied to the urban region of Berlin, Germany, to investigate and compare the occurrence and duration of HWs, and their long‐term trends from 1893 to 2017. We studied how long‐term trends depend on different definition of HWs, as well as if long‐term mean values and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 80 publications
3
43
0
Order By: Relevance
“…Urban Rural arise when heat wave definitions applying daily minimum or daily mean T are investigated. These contrasts could not be found when using heat wave definitions that apply daily maximum T (Fenner et al 2019). Note that given the diverse findings in other studies concerning UHIIs during HWEs, our findings might not be transferable to other regions, as only one mid-latitude city was investigated.…”
Section: Identification Locationmentioning
confidence: 54%
See 2 more Smart Citations
“…Urban Rural arise when heat wave definitions applying daily minimum or daily mean T are investigated. These contrasts could not be found when using heat wave definitions that apply daily maximum T (Fenner et al 2019). Note that given the diverse findings in other studies concerning UHIIs during HWEs, our findings might not be transferable to other regions, as only one mid-latitude city was investigated.…”
Section: Identification Locationmentioning
confidence: 54%
“…Similarly, Fenner et al (2019) showed that in Berlin urban-rural contrasts in heat wave characteristics only Table 1. Mean differences (Δ) in weather conditions between hot weather episodes (HWEs) and normal conditions (NC) during 2015-2018, May-September.…”
Section: Discussion Of the Effect Of Definition Of Hwesmentioning
confidence: 96%
See 1 more Smart Citation
“…They devised a HW hazard index and found that most of the capitals revealed significant positive trends of HW hazard characteristics especially in central-eastern and southeastern Europe. They also concluded that minor index increases were observed in most of the northern capitals and decreases in several northern and especially southwestern cities.Fenner et al [17] applied different HW definitions to study long-term (1893-2017) trends of HW duration and frequency for Berlin. They found a general positive trend amongst HW definitions but with the respective magnitude depending on the definition and trend estimation method.…”
mentioning
confidence: 99%
“…Fenner et al [17] applied different HW definitions to study long-term (1893-2017) trends of HW duration and frequency for Berlin. They found a general positive trend amongst HW definitions but with the respective magnitude depending on the definition and trend estimation method.…”
mentioning
confidence: 99%